Impact of a sustained TPSR program on students’ responsibility, motivation, sportsmanship, and intention to be physically active - Merino-Barrero, Juan Andrés; Pedreño, N.; Valero-Valenzuela, A.; Fernández-Río, Javier (Journal of Teaching in Physical Education, 2020)
Purpose: To assess the impact of a sustained Teaching for Personal and Social Responsibility program in Physical Education. Method: There were 72 primary and secondary education students (11–13 years), enrolled in two different schools, and their four teachers were randomly distributed into an experimental group (n = 35) and a nonequivalent group (n = 37) by their schools’ administration. A pre-/posttest, repeated-measures nonequivalent group design was used. The two teachers of the experimental group implemented a Teaching for Personal and Social Responsibility program, whereas the two teachers of the nonequivalent group used Direct Instruction in their classes over four consecutive learning units (29 sessions, 5 months). Results: Students in the experimental group significantly increased their personal and social responsibility (p < .01), self-determined motivation (p < .01), basic psychological needs satisfaction (competence, autonomy, and relatedness; p < .01), sportsmanship (p < .05), and intention to be physically active outside school (p < .05). Conclusion: The Teaching for Personal and Social Responsibility program was more able to increase students’ self-determined motivation and to generate positive psychosocial consequences than the Direct Instruction approach.
Keywords: fidelity of implementation; instructional models; physical education; self-determination theory; Scopus; JCR